Survey of economic conditions in Africa: 1987-1988 - United Nations (New York : United Nations, 1990)
The book contains the report of the survey carried out by the Economic Commission for Africa of the United Nations on the economic situation in 1988 and the prospects for 1989.
Includes bibliographical references.
usc 18/04/2019
Ref.
Keywords: National income; Economic history; Economic conditions; Economic planning; Trade, International; Social conditions; Africa